Discrete Pulses of Cooler Deep Water Can Decelerate Coral Bleaching During Thermal Stress: Implications for Artificial Upwelling During Heat Stress Events - Sawall, Yvonne; Harris, Moronke; Lebrato, Mario; Wall, Marlene; Feng, Ellias Yuming (Frontiers in Marine Science, 2020)
Global warming is considered to be the most severe threat to coral reefs globally, which makes it important for scientists to develop novel strategies that mitigate the impact of warming on corals and associated habitats. Artificial upwelling of cooler deep water to the surface layer may be a possible mitigation/management tool. In this study, we investigated the effect of simulated artificial upwelling with deep water off Bermuda collected at 50 m (24°C) and 100 m (20°C) on coral symbiont biology of 3 coral species (Montastrea cavernosa, Porites astreoides, and Pseudodiploria strigosa) in a temperature stress experiment. The following treatments were applied over a period of 3 weeks: (i) control at 28°C (ii) heat at 31°C, (iii) heat at 31°C + deep water from 50 m depth, and (iv) heat at 31°C + deep water from 100 m depth. Artificial upwelling was simulated over a period of 25 minutes on a daily basis resulting in a reduction of temperature for 2 hours per day and the following degree-heating-weeks: 5.7°C-weeks for ii, 4.6°C-weeks for iii and 4.2°C-weeks for iv. Comparative analysis of photosynthetic rate, chlorophyll-a concentration and zooxanthellae density revealed a reduction of heat stress responses in artificial upwelling treatments in 2 of the 3 investigated species, and a stronger positive effect of 100-m water than 50-m water. These results indicate that artificial upwelling could be an effective strategy to mitigate coral bleaching during heat stress events allowing corals to adjust to increasing temperatures more gradually. It will still be necessary to further explore the ecological benefits as well as potential ecosystem impacts associated with different artificial upwelling scenarios to carefully implement an effective in-situ artificial upwelling strategy in coral reefs.